PANDANGAN ANTROPOLOGI TERHADAP PRAKTIK AKAD MUSYARAKAH DAN PROBLEMATIKANYA DI LEMBAGA KEUANGAN SYARIAH - HAMZAH, MOH.; SARI, EKA PERMATA (Universitas Muhammadiyah Surabaya, 2023)
This research will comprehensively answer, describe, and explain in detail the context of problems that occur in musyarakah contracts. Therefore, this research will reveal the veil of understanding by focusing on the anthropological view of the implementation of musyarakah contracts, both in terms of the application of the contract and sharia principles, as well as the problems that often occur in musyarakah contracts in the operations of sharia financial institutions. This research is a type of normative-empirical research, which is an anthropological approach. The data used are primary and secondary data which are then analyzed using argumentative analysis techniques. The results and conclusions of this research are that musyarakah exists as a method for practicing and implementing Islamic religious values, where this also includes the concept of hifdz mall (maintenance of assets) which is essentially part of the objectives of sharia itself. Although problems often occur in the musyarakah contracts carried out intentionally by the parties or unpredictable force majeure, these musyarakah contracts can be maximized again by using good and correct solutions by Sharia financial institutions. With the concept of the musyarakah contract, Sharia financial institutions have a mission to fight ignorance, poverty, tyranny, evil, and injustice in economic activities to achieve al-falah (prosperity in this world and the hereafter).